Sigmund Freud - Sándor Ferenczi. Briefwechsel Band III/2: 1925-1933 - Brabant, Eva (2005)
This sixth and final half-volume of the Freud/Ferenczi correspondence covers the period from 1925 until Ferenczi's death in 1933. During that period, Freud works on revisions of psychoanalytical theory, on autobiographical and historical contributions, on religious topics and on his critique of civilization and culture, and on the development of female sexuality. Ferenczi publishes his probably most interesting, but also most contested contributions to the theory and technique of psychoanalysis. With hindsight one can say that his technical experiments lead him to formulate a theoretical model which has became the basis for contemporary theories. For a time, he closely collaborates for this with Freud's "right hand," Otto Rank. Their publications lead to a personal and scientific fight over power between the leaders of the psychoanalytic movement, a fight that threatens to split that very movement. This conflict - which has influenced the history of psychoanalysis to this day - results in Rank's leaving the psychoanalytic community and Ferenczi's being marginalized. Freud, at first supportive of Ferenczi and Rank, eventually joins their opponents (above all Karl Abraham and Ernest Jones). He regards Ferenczi's innovations as a scientific regression, and interprets them as Ferenczi's reaction to his own personal problems and deficits. Ferenczi himself, however, is convinced of the value of his ideas, and struggles for more independence from Freud. The general tone of their letters gets less intimate, and sometimes outright sharp. Ferenczi writes less often, instead he confides his new ideas and his criticism of Freud to his "Clinical Diary." Although an open break can be avoided, Ferenczi's untimely death prevents a resolution of their conflicts and misunderstandings. Without doubt, the Freud/Ferenczi correspondence is one of the most important primary sources for the early history of psychoanalysis, and it is a literary event of the first magnitude to boot. In none of his other correspondences with disciples writes Freud so frequently, so openly, and over such a long period of time. This final volume documents the tragic end of this "intimate community of life, feeling, and interest" (Freud to Ferenczi, 11.1.1933); and all this before the background of the political and social upheaval of that time. The guiding line of the editorial apparatus has been to give the contemporary reader information about anything with which she or he might not be familiar: persons, events, literary and scientific works, quotations, cryptoquotations, allusions, and so on. It also contains quotations from a great number of hitherto unpublished Freud letters.